Topologie: 26. August bis 3. September 1964 - Puppe, Dieter; Dold, Albrecht; Schubert, Horst (Tagungsbericht, 1964)
J. F. Adams, Manchester; M. Arkowitz, Princeton; F. W. Bauer, Frankfurt a. M.; W. Bos, Heidelberg; H. - B. Brinkmann, Saarbrücken; E. Brown, Waltham; H. Cartan, Paris; C. R. Curjel, Princeton; T. tom Dieck, Saarbrücken; E. Dyer, Chicago; S. Eilenberg, New York; D. A. Epstein, Coventry; A. Frei, Zürich; J. W. Gray, Urbana; C. Hanner, Solna; H. Holmann, Münster; H. Ibisch, Paris; L. Ilusie, Paris; K. Jänich, Bonn; F. Kamber, Zürich; L. Kristensen, Aarhus; K. Lamotke, Bonn; S. Mardešić, Zagreb; W. S. Massey, New Haven